A cephalometric evaluation among Filipino adults aged 18-30 years using the denture frame analysis (DFA), overbite depth indicator (ODI) and anteroposterior dysplasia indicator (APDI) - Lazaro, Marie Joy R.
A cephalometric study of Filipino subjects aged 18-30 years with normal occlusion and esthetic profile using the Denture Frame Analysis, Overbite Depth Indicator and the Anteposterior Dysplasia Indicator. The subjects in the study sample consisted of 22 males and 28 females. Means and standard deviations were established and statistical analysis was performed to compare the Filipino cephalometric mean values with the Japanese and Caucasians. Comparison of the derived Filipino cephalometric means with the Japanese showed 3 statistically significant parameters namely the OP-MP angle, intermolar and APDI. Whereas, most of the Filipino cephalometric mean values were statistically significant when compared to Caucasians except for FH-MP, OP-MP and AB-MP angles. Findings showed that Filipinos in this study present a lesser convex skeletal profile due to the more anteriorly-positioned mandible. However, Filipinos exhibit a relatively protrusive and proclined maxillary and mandibular incisors. It was concluded that the DFA, ODI and APDI were capable of describing the sagittal and vertical relationships of the cranifacial complex among the 3 racial groups. These parameters may be considered as adjunctive tools in conjunction with other cephalometric analyses for orthodontic differential diagnosis.